2018
DOI: 10.20507/maijournal.2018.7.2.6
|View full text |Cite
|
Sign up to set email alerts
|

Oranga mokopuna: A tāngata whenua rights-based approach to health and wellbeing

Abstract: Rights-based approaches to health in Aotearoa New Zealand have increased in recent years. However, dominant Westernised conceptualisations of rights have been criticised for their ties to colonialism and individualistic focus. This paper presents Oranga Mokopuna as an alternative which disrupts Western notions of rights that are assumed to have universal application. Based in Te Ao Mäori, Oranga Mokopuna provides a conceptual frame of reference for the realisation of tängata whenua rights to health and wellbei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(26 citation statements)
references
References 8 publications
0
26
0
Order By: Relevance
“…The International Journal of Children's Rights (2023) 1-37 of Oranga Mokopuna, suggested as an alternative approach to health rights of Māori children and their families, which challenges the "Western" notions of rights (King, et al, 2018).…”
Section: 2mentioning
confidence: 99%
“…The International Journal of Children's Rights (2023) 1-37 of Oranga Mokopuna, suggested as an alternative approach to health rights of Māori children and their families, which challenges the "Western" notions of rights (King, et al, 2018).…”
Section: 2mentioning
confidence: 99%
“…This finding can be broadened to other indigenous peoples, whose voices tend to be excluded from policies. The right of children to be involved in decision-making is recognised in UNCRC as well as the collective decision-making process used by Māori [ 1 , 43 ]. While there is limited research in NZ, one study related to children’s perceptions of food marketing and what to do about it, found that children were able to suggest credible solutions to address issues of concern [ 74 ].…”
Section: Discussionmentioning
confidence: 99%
“…Health inequities between Māori and non-Māori, including obesity and food insecurity, are evidence of the Crown’s failure to uphold indigenous rights [ 42 ]. This is a breach of NZ’s founding document, the Treaty of Waitangi [ 43 ]. The Treaty is a partnership agreement signed in 1840 between Māori and the British Crown that ultimately enabled the establishment of government in NZ, and guaranteed to Māori, equal benefits of citizenship.…”
Section: Introductionmentioning
confidence: 99%
“…Relationality and relational practices emerged as a key dimension in a majority of the publications. Eighteen of the 24 publications highlighted the importance of honouring Indigenous worldviews and holistic understandings of the relationships and relational processes within and between families, communities, ancestors and the natural environment (Cameron, 2010;Gerlach & Gignac, 2019;Grace et al, 2018;Hamley et al, 2023;Hansen, 2012;Johnson et al, 2015;King et al, 2018;Lawton et al, 2020;Lucero & Leake, 2016;Makokis et al, 2020;Moss & Lee, 2019;Napoli & Gonzalez-Santin, 2001;Onnis et al, 2020;Robinson et al, 2017;Satour & Goldingay, 2021;Ullrich, 2020;van Schilfgaarde & Shelton, 2021;Zinga, 2012). This strong emphasis on relationality spanned geographic locations.…”
Section: Relationalitymentioning
confidence: 99%